Prediction of the remaining service lifetime of inflatable rubber dam with deep hole damage - Budiman, Bentang Arief; Sambegoro, Poetro Lebdo; Rahardian, Samuel; Ilhamsyah, Rizky; Firmansyah, Ridha; Juangsa, Firman Bagja; Aziz, Muhammad (Universitas Pendidikan Indonesia, 2020)
This paper exhibits a method to predict the remaining service lifetime of inflatable rubber dam by considering the appearance of deep hole damage. The material used for the rubber dam is a composite comprising three layers of woven fabric as fiber and EPDM/SBR 64 474 rubber as a matrix. The service lifetime is predicted by calculating the degradation of rubber dam’s material properties. Simple Rate Law model and Time-Temperature Superposition model are employed to calculate the rubber properties degradation. A finite element analysis is then conducted to investigate stress and strain distributions which occur in the rubber dam membrane during operational loading. Furthermore, the effect of deep hole damage in the rubber dam, which is caused by improper maintenance, is modeled as well. The results show that a 7 mm depth of the hole can accelerate rubber degradation, which causes catastrophic failure. This can happen because two layers of the woven fabric in the rubber dam have been broken. Suggestion to hold up the degradation is also discussed.